ANALISA DAMPAK PENGEMBANGAN KARIR DAN MOTIVASI TERHADAP KINERJA PEGAWAI (STUDI KASUS DINAS KOPERASI DAN UMKM KABUPATEN KERINCI) - Ferry Siswadhi; Sudirman Sudirman (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2018)
This research is aimed to find out the influence of career developmentand motivation on the performance of employees taking case study at DinasKoperasi and UMKM Kerinci both partially and simultaneously, and also to findout how much influence partially and simultaneously. Using Likert scaleanalysis tools and multiple linear regression analysis. The number of samplesresearched as many as 41 people which is also the total population of employeesof Dinas Koperasi and UMKM Kabupaten Kerinci. The result of the research iseither partially or simultaneously the variable of career development andmotivation have an effect on significantly to employee performance. Theconclusion obtained through this research is, the need for increased coachingactivities for employees, such as technical guidance, coordination meetings andso on.